Experimenting with a Multi-User Virtual Environment for Collaborative Online International Learning: A Case Study from Ireland and Norway - Slattery, Darina M.; Cleary, Yvonne; Giæver, Tonje Hilde; Engen, Bård Ketil (Nordic Journal of Comparative and International Education (NJCIE), 2025)
This study applies Computer Supported Collaborative Learning (CSCL) as an analytical lens to explore the extent to which a Multi-User Virtual Environment (MUVE) platform could facilitate collaboration within the context of the Collaborative Online International Learning (COIL) framework. Students from University of Limerick (UL) and Oslo Metropolitan University (OsloMet), used the OpenSimulator MUVE platform for collaboration. The students were divided into four groups comprising a mix of students from both universities. Methodologically, this case study is informed by pre- and post- survey data, screen recordings from two plenary sessions, as well as a final oral presentation and discussion in OpenSimulator. Findings show mixed experiences by the students and point to three pillars of project design that can facilitate CSCL: the platform, the international dimension, and opportunities for collaboration. While students reported that being represented as an avatar had some positive affordances over other video-based platforms, students also faced usability challenges with the platform. In terms of internationalisation and collaboration, students valued working with peers from another country, with their interactions mediated by a platform they otherwise would not have used. Overall, findings show that factors such as time, the usability of the MUVE platform, the assigned task, and the international dimension, are all essential considerations when using a MUVE to facilitate COIL projects.